Age 83 is not a hindrance Dr. Jahid gets a second PhD - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA BESAR, 5 November 2022 - A sense of responsibility to empower the practice of Islamic medicine became the reason for Dr. Haji Jahid Sidek to complete his second doctoral thesis (PhD) at Universiti Malaysia Pahang (UMP).